Vagus nerve assessment via ultrasonography in irritable bowel syndrome. Are there any changes of dimension in the vagus nerve? - Özçağlayan, Ömer; Kurtoğlu Özçağlayan, Tuğba İlkem; Doğru, Mücahit; Mete, Rafet (Turkish Journal of Gastroenterology, 2020)
Background/Aim: Irritable bowel syndrome (IBS) is the functional gastrointestinal disorder which has closely relationship with Central Nervous System (CNS). VN is the major connector between CNS and Enteric Nervous System (ENS). The aim of this study was to investigate the possible changes of dimension of Vagus Nerve (VN) with Vagus ultrasonography (VU) in IBS.Material and Methods: A total 119 patients which is consisted of 66 IBS patients appropriated with Rome IV criterias and 53 patients of control group were enrolled to the study. All patients were underwent to colonoscopy for role-out the organic pathologies, such as polyposis, inflammatory bowel syndromes, diverticulosis and colon cancer. Right Vagus (RV) and left Vagus (LV) nerve areas and diameters were calculated with VU.Results: There were no statistical difference of RV (p=0.445) and LV (p=0.944) diameter between two groups. There were also no statistical difference of RV (p=0.549) and LV (p=0.874) areas between IBS and control groups.Conclusion: VU clearly depicted that there is no changes of dimension in VN areas and diameters in the IBS. This might show that VN is only a transporter of abnormal neuronal stimulations according to IBS pathophisiology.